African Primary Care Research: Quantitative analysis and presentation of results - Bob Mash; Gboyega A. Ogunbanjo (AOSIS, 2014)
This article is part of a series on Primary Care Research Methods. The article describes types of continuous and categorical data, how to capture data in a spreadsheet, how to use descriptive and inferential statistics and, finally, gives advice on how to present the results in text, figures and tables. The article intends to help Master's level students with writing the data analysis section of their research proposal and presenting their results in their final research report.